Analisis Metabolit Sekunder Daun Brucea javanica [L] Merr dari Dua Tempat Berbeda di Pulau Timor - Yasa, Julita Dewitri Mertha; Jacob, Jois Moriani (JURNAL KAJIAN VETERINER, 2024)
The leaves of Brucea javanica [L] Merr have long been utilized as an alternative medicine for a variety of illness. Although a number of investigations have been conducted to ascertain the advantages and composition of secondary metabolites in this plant's leaves, nothing has ever been published on the particular study conducted on the island of Timor. The purpose of this study was to ascertain which secondary metabolites were present in the leaves of this plant that was grown in two distinct locations on Timor Island. The findings of this study will be used as an empirical basis for future investigations into the use of herbal remedies. The study's findings demonstrated that while flavonoids and alkaloids weren't present from the plant's ethanol extract, it did contain highly concentrated terpenoids and tannins at both locations. In contrast, saponin content was only discovered in leaves collected from the neighbourhood of Fatumnutu. The spectrophotometer test revealed that the ethanol extract of Bruce planta javanica [L] Merr from Noelbaki Village had a greater secondary metabolite absorption value compared to plant extract from Fatumnutu Village. The absorption values for tannin and alkaloid showed the largest overall variation in absorption levels, varying by around 0.513% and 0.68% for each constituent. In the meantime, there is a 0.513% variation in tannin compounds between the two sites. In order to ascertain the bioactivity of this plant's leaf extract for the creation of herbal medicines in Indonesia, more investigation is required into the variations in saponin levels and absorbency levels of secondary metabolite compounds from the two locations.